231k views
3 votes
Which expression is equivalent to (x^4/3 x^2/3)^1/3?

Which expression is equivalent to (x^4/3 x^2/3)^1/3?-example-1

2 Answers

5 votes
The answer is B, x^2/3
User Tikeb
by
5.6k points
2 votes

Answer : The correct option is,
x^{(2)/(3)}

Step-by-step explanation :

The given expression is :


(x^{(4)/(3)}* x^{(2)/(3)})^{(1)/(3)}

First we have to solve the term present in the bracket.

Identity used :
x^a* x^b=x^((a+b))


\Rightarrow (x^{((4)/(3)+(2)/(3))})^{(1)/(3)}

By the adding the powers of 'x', we get:


\Rightarrow (x^{(6)/(3)})^{(1)/(3)}


\Rightarrow (x^(2))^{(1)/(3)}

Now we have to use identity
(x^(a))^b=x^(ab), we get :


\Rightarrow (x)^{(2* (1)/(3))}


\Rightarrow (x)^{(2)/(3)}

Therefore, the correct option is,
x^{(2)/(3)}

User Hybrid
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.